2017
DOI: 10.1101/121376
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Response of microbial community function to fluctuating geochemical conditions within a legacy radioactive waste trench environment

Abstract: During the 1960s, small quantities of radioactive materials were co-disposed with chemical waste at the Little Forest Legacy Site (Sydney, Australia) in three-metre-deep, unlined trenches. Chemical and microbial analyses, including functional and taxonomic information derived from shotgun metagenomics, were collected across a six-week period immediately after a prolonged rainfall event to assess how changing water levels impact upon the microbial ecology and contaminant mobility. Collectively, results demonstr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 91 publications
0
16
0
Order By: Relevance
“…Additional metadata is provided as derived from MGnify or the original studies. The column 'Reference' indicates the source study, corresponding to references (Simon et al, 20162009;Eiler et al, 20162014;Nielsen et al, 20172014;Staley et al, 20182014;Brown et al, 2015;Hugerth et al, 2015;Sunagawa et al, 2015;Yan et al, 2015;Bendall et al, 2016;Meziti et al, 2016;Seitz et al, 2016;Toyama et al, 2016;Tsementzi et al, 2016;Vázquez-Campos et al, 2017;Linz et al, 2018), or 'Unpublished' corresponding to data publicly available in the SRA/ENA databases but not currently linked to publications. Table S5: Correlation tests performed between genomospecies features and ecologic breadth metrics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional metadata is provided as derived from MGnify or the original studies. The column 'Reference' indicates the source study, corresponding to references (Simon et al, 20162009;Eiler et al, 20162014;Nielsen et al, 20172014;Staley et al, 20182014;Brown et al, 2015;Hugerth et al, 2015;Sunagawa et al, 2015;Yan et al, 2015;Bendall et al, 2016;Meziti et al, 2016;Seitz et al, 2016;Toyama et al, 2016;Tsementzi et al, 2016;Vázquez-Campos et al, 2017;Linz et al, 2018), or 'Unpublished' corresponding to data publicly available in the SRA/ENA databases but not currently linked to publications. Table S5: Correlation tests performed between genomospecies features and ecologic breadth metrics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the metagenomes sequenced as part of our study, we used previously reported metagenomes from other sites and environments for comparisons. These metagenomes, derived from previous studies (Simon et al, 2009;Eiler et al, 2014;Nielsen et al, 2014;Staley et al, 2014;Brown et al, 2015;Hugerth et al, 2015;Sunagawa et al, 2015;Yan et al, 2015;Bendall et al, 2016;Meziti et al, 2016;Seitz et al, 2016;Toyama et al, 2016;Tsementzi et al, 2016;Vázquez-Campos et al, 2017;Linz et al, 2018), or recovered via MGnify (Mitchell et al, 2016), are described in Table S4. The raw reads were obtained from the European Nucleotide Archive (EBI ENA) and processed as described above.…”
Section: Samples From Other Projectsmentioning
confidence: 99%
“…Next Generation Sequencing‐based metagenomics and metatranscriptomics have revolutionized the methodologies to decipher the diversity of microorganisms, community characteristics, and metabolic activity in different environments (Tringe et al ; Ventosa et al ) by obviating the need for the isolation and culture of microorganisms (Handelsman et al ; Chen and Pachter ). Both metagenome and metatranscriptome contribute significantly to appreciate the microbial processes and community functionalities in biogeochemistry, including groundwater (Einsiedl and Mayer ; Long et al ; Coutinho et al ; Vazquez‐Campos et al ). In comparison with DNA microarrays or qPCR, high throughput metagenome and metatranscriptome profiling can also capture more comprehensive picture of resistome in the groundwater (Luo and Angelidaki ; Li et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Since its closure, the periodic occurrence of intense rainfall events leads to the filling of the former trenches with surface waters, which, depending on preceding conditions, can result in the trench water discharging into the surface and near-surface soils in a ‘bath-tub’-like mechanism (Payne et al, 2013, 2020). Aside from providing a mechanism enabling the export of contaminants from the legacy trenches (Payne et al, 2013), the periodic influx of oxic waters into these natural reducing zones results in transitory microbial population shifts associated with pronounced elemental cycling (Vázquez-Campos et al, 2017; Kinsela et al, 2021). Our previous research showed that the archaeal community in the LFLS waste trenches, while constituting a minor portion of the whole microbial community, included a number of potentially interesting members, either in terms of phylogeny and/or functionality (Vázquez-Campos et al, 2017).…”
Section: Introductionmentioning
confidence: 99%